Лінгвопоетичні виміри сучасного текстотворення - Кононенко, В.І. (Мовознавство, 2013)
Відзначає свій ювілей відомий мовознавець і лінгводидакт доктор філологічних наук, професор, академік Національної академії педагогічних наук України, заслужений діяч науки і техніки Віталій Іванович Кононенко. Перу вченого належить понад 450 наукових
праць у галузі українського і слов’янського мовознавства, зокрема монографії «Символи
української мови» (1996), «Концепти українського дискурсу» (2004), «Мова в контексті
культури» (2008), «Текст і смисл» (2012), серія підручників і навчальних посібників. Редакція
журналу «Мовознавство» щиросердечно вітає ювіляра й зичить йому нових
творчих здобутків.
У статті розглянуто активні процеси творення українських художніх текстів. Проаналізовано
мовно-естетичні засоби, що відбивають тенденції розвитку красного письменства.
Висвітлено типологічні риси ідіолектів сучасних майстрів слова. In the article modem processes of Ukrainian fiction texts are examined through the
linguo-poetic dimension. In the aspects of linguo-pragmatics functions of linguistic culturemas
and keywords as linguistic and aesthetic signs are defined. Inventory of typological resources of
figurative and metaphorical word use implies its realization in a system of concepts, scripts,
verbal symbols, etc. with focus on individual author’s idiolects distinguishing.
Active processes of transformation of traditional figurative-expressive means assist in new
visions of discourse modeling principles. The structure of figurative usage undergoes changes
that manifest themselves in a critical assessment of the artistic speech achievements in previous
periods, in search of more effective expressive means. In linguistic and aesthetic field,
especially in poetry, processes of presentation intellectualization, peculiar text encoding are
defined.
Retrieval of renewed fiction language style is based on elements combination of folk
language culture and directed to semantic complexity innovative methods of text formation,
establishing the underlying associative parallels, new symbolization. There is a practice of
metaphorical transformation as a result of motivational deformation, antinomic and allusive
convergence, shifts in the context environment. One of the distinct techniques in symbolization
is the use of personalized images.
In the examples of rethinking traditional symbols of land, wings, homes and others it is
shown the loss of former imaginative comprehension, the phenomenon of «flashing» meanings.
Significant changes characterize structuring texts, the processes of presentation
conceptualization, use of «vertical» context. System of accustomed images that reflect the
lingual world picture of Ukrainians is shifted. Texts as entire metaphors, sophisticated
understatements are getting spread, in poetic language implicitness, figurative word set
encoding, reveals itself that complicates the interpretation of meaning. At the same time, signs
of speech individualization, image system creation, which stands out for the search of new
linguo-thinking are observed in a creative manner of leading Ukrainian writers.